A Randomized Trial of Foley Balloon Induction of Labor Trial in Multiparas (FIAT-M) - Connolly, Katherine A.; Kohari, Katherine S.; Factor, Stephanie H.; Rekawek, Patricia; Miller, Meredith R.; Smilen, Brooke S.; Stone, Joanne L.; Bianco, Angela T. (American Journal of Perinatology, 2017)
Background The optimal method of labor induction is not known. It is important to determine the safest and efficient method to minimize the length of labor, hospital stay, cost, and adverse outcomes.Objective This study aims to determine if induction of labor with simultaneous use of oxytocin and Foley balloon versus the sequential use of Foley balloon followed by oxytocin decreases the time to delivery in multiparous women.Study Design We conducted a randomized controlled trial of multiparous women who presented for induction of labor at Mount Sinai from December 2013 to April 2016. Patients were admitted for induction with indications determined by their provider. Women with a nonanomalous, singleton fetus ≥ 24 weeks in vertex presentation with intact membranes were offered participation. Exclusion criteria included the history of uterine surgery, unexplained vaginal bleeding, latex allergy, or contraindication to vaginal delivery. Participants were randomized to either simultaneous (oxytocin and Foley balloon) or sequential (oxytocin after the expulsion of Foley balloon) induction group. The primary outcome was the time from induction to delivery. Secondary outcomes included mode of delivery, estimated blood loss (EBL), postpartum hemorrhage (PPH), chorioamnionitis, and composite neonatal outcome. Maternal and neonatal outcomes were collected via chart review. Analyses were done on an intention-to-treat basis.Results A total of 142 patients were enrolled; 75 in the simultaneous and 67 in the sequential group. There were no differences in baseline characteristics in the two groups. There was no difference in median time to delivery between groups (10.7 vs. 10.6 hours, p = 0.44). There was no difference in the rate of cesarean delivery, EBL, PPH, chorioamnionitis, or composite neonatal outcome.Conclusion Simultaneous use of oxytocin and Foley balloon for induction of labor does not decrease time to delivery in multiparas.
Keywords: Foley balloon; induction of labor; oxytocin